2015
DOI: 10.1093/ecco-jcc/jjv145
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurine Therapy Reduces the Incidence of Colorectal Neoplasia in Patients with Ulcerative Colitis. Data from the ENEIDA Registry

Abstract: The risk of AN among UC patients is lower than previously reported but steadily increases from the time of UC diagnosis. The widespread use of thiopurines may have influenced this reduced incidence of UC-related neoplasias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 56 publications
1
42
4
Order By: Relevance
“…Twenty‐one studies contributed data specific for UC, while only five studies for CD . The reduction in CRN risk associated with 5‐ASA use was 50% among UC patients (RR = 0.50, 95% CI: 0.38–0.64), but weaker and nonsignificant among patients with CD (RR = 0.76, 95% CI: 0.43–1.33) (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐one studies contributed data specific for UC, while only five studies for CD . The reduction in CRN risk associated with 5‐ASA use was 50% among UC patients (RR = 0.50, 95% CI: 0.38–0.64), but weaker and nonsignificant among patients with CD (RR = 0.76, 95% CI: 0.43–1.33) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐one studies evaluated the association of 5‐ASA with CRC risk, while five studies reported data for dysplasia. Exposure to 5‐ASA was significantly associated with a protective effect against both outcomes (cancer: RR = 0.58, 95% CI: 0.45–0.74, Figure ; dysplasia: RR = 0.54, 95% CI: 0.35–0.84, Figure ) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In a meta analysis, quantitative estimates of CRC risk in UC have been reported to be 2% after 10 years, 8% after 20 years, and 18% after 30 years of disease[58]. More recent data (2015) has found a cumulative risk of advanced neoplasia in UC of 2%, 5.3% and 14.7% at 10, 20 and 30 years, respectively[59]. In addition, numerous cohort studies on CRC in UC have noted a relationship between CRC risk with the extent of disease, with a standardized incidence ratio (SIR) of 1.7 for proctitis, 2.8 for left-sided colitis, and 14.8 for pancolitis[60].…”
Section: Thiopurines In Chemopreventionmentioning
confidence: 99%
“…Further support for a protective effect of thiopurines was established using data from the ENEIDA registry (Estudio nacional en Enfermedad Inflamatoria Intestinal sobre determinantes genéticos y ambientales), a nationwide, hospital-based, prospectively maintained, Spanish database of incident and prevalent IBD patients[59]. In this study of 831 patients with UC with 26 cases of CRC and 29 cases of high-grade dysplasia, use of thiopurines (OR = 0.21, 95%CI: 0.06-0.74, P = 0.015) and being in a surveillance colonoscopy program (OR = 0.33; 95%CI: 0.16-0.67; P = 0.002) were independent protective factors for advanced neoplasia[59].…”
Section: Thiopurines In Chemopreventionmentioning
confidence: 99%
See 1 more Smart Citation